Sex differences in self-reported delinquency and official records: A multiple-group structural modeling approach - Sampson, Robert J. (Journal of quantitative criminology, 1985)
There has been a large increase in research in the last 10 years or so on the nature, extent, and causes of female delinquency, especially on how patterns differ from those of male delinquency. Few research efforts, however, have systematically examined sex differences in the reliability and construct validity of the most common technique used in causal research-the self—report method. The present study addresses this issue by empirically examining male-female differences in self-report reliabilities and the effect of the prevalence and incidence of delinquent behavior on official contact (i.e., arrest, court referrals). Multiple-group covriance structure models are employed to test hypotheses of measurement and structural invariance. The major conclusion is that while self-report measurement parameters (e.g., reliabilities) may differ, the structural link between the prevalence and incidence of delinquent behavior and official contact is generally invariant with respect to sex.